2005
DOI: 10.1021/ja0506410
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Ruthenium-Catalyzed Anti-Markovnikov Hydroamination of Vinylarenes:  Intermediates and Evidence for Catalysis through π-Arene Complexes

Abstract: Studies are described that reveal the steps of the anti-Markovnikov hydroamination of vinylarenes with alkylamines catalyzed by Ru(COD)(2-methylallyl)2, bis(diphenylphosphino)pentane, and TfOH. Treatment of the catalyst components with an excess of styrene under the catalytic reaction conditions afforded a new ruthenium eta6-styrene complex with an ancillary tridentate PCP ligand. This ruthenium complex was active as catalyst for the hydroamination of styrene with morpholine to give the anti-Markovnikov adduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(67 citation statements)
references
References 23 publications
2
63
0
2
Order By: Relevance
“…Mechanistic investigations have shown that in this case, the nucleophilic attack of the formally anionic ligand is the turnover-limiting step [95,115,132], and indeed, many η 3 -allyl/benzyl complexes have been identified when monitoring such reactions [94,115,132]. Both the reaction rate and the site of nucleophilic attack can be attenuated with judicious ligand selection [56,105,132]. For example, chelating diphosphines with large bite angles are known to destabilize the η 3 -allyl complexes and render them more susceptible to nucleophilic attack, thereby resulting in enhanced reactivity [132].…”
Section: Nucleophilic Attack On Allylic Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic investigations have shown that in this case, the nucleophilic attack of the formally anionic ligand is the turnover-limiting step [95,115,132], and indeed, many η 3 -allyl/benzyl complexes have been identified when monitoring such reactions [94,115,132]. Both the reaction rate and the site of nucleophilic attack can be attenuated with judicious ligand selection [56,105,132]. For example, chelating diphosphines with large bite angles are known to destabilize the η 3 -allyl complexes and render them more susceptible to nucleophilic attack, thereby resulting in enhanced reactivity [132].…”
Section: Nucleophilic Attack On Allylic Complexesmentioning
confidence: 99%
“…With styrene derivatives, the Markovnikov product is commonly obtained, as rationalized by the proposed mechanism. However, reliable methods for obtaining the anti-Markovnikov product have been developed using Ru-catalyzed hydroamination of vinyl arenes, in which η 6 -arene complexes are key catalytic intermediates (Scheme 15.17) [105,133]. This species promotes a nucleophilic attack at the β-carbon atom and catalytic turnover is achieved to realize selective anti-Markovnikov hydroamination with select amine nucleophiles [133].…”
Section: Nucleophilic Attack On Allylic Complexesmentioning
confidence: 99%
“…[113] In contrast, aryl halides substituted by alkoxy groups (well known to decrease the electron affinity of these substrates) have repeatedly been reported as providing good yields of Grignard reagents. [114,115] Note, however, that the preparation of nitroaromatic Grignard reagents is feasible by halogen-magnesium exchange. [116] Our first entry into the field of comparing the S RN 1 and Grignard reagent formation mechanisms was motivated by observations of metal-vapour-synthesised magnesium reacting with alkyl halides.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Significant research activity has focused on the use of late-transition-metal complexes for intermolecular hydroamination reactions of olefins, featuring iridium, [10][11][12] rhodium, [13][14][15][16][17][18] nickel, [19,20] palladium, [21][22][23][24] platinum, [25,26] and ruthenium. [27,28] The high cost of these complexes, their stabilizing ligands, or the additives constitute a limitation of these protocols. Recently, we reported a Group 4 metal catalyzed [29] intermolecular [30] hydroamination of norbornene.…”
mentioning
confidence: 99%